Optimal Tilts: Combining Persistent Characteristic Portfolios. Issue 4 (1st October 2017) - Baker, Malcolm; Taliaferro, Ryan; Burnham, Terence
Abstract : We examine the optimal weighting of four tilts in US equity markets over 1968–2014. We define a "tilt" as a characteristics-based portfolio strategy that requires relatively low annual turnover. This definition forms a continuum, with small size, a very persistent characteristic, at one end of the spectrum and high-frequency reversal at the other. Unlike with low-turnover tilts, a full history of transaction costs is essential for determining the expected return of, and thus the optimal allocation to, less persistent, more turnover-intensive characteristics. The mean–variance-optimal tilts toward value, size, and profitability are roughly equal to each other and to the optimal low-beta tilt. Notably, the low-beta tilt is not subsumed by the other three. Abstract : Disclosure: Ryan Taliaferro is a senior vice president at Acadian Asset Management. Malcolm Baker serves as a consultant to Acadian Asset Management and also acknowledges support from the Division of Research at Harvard Business School. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research or Acadian Asset Management. The views expressed herein should not be considered investment advice and do not constitute or form part of any offer to issue or sell, or any solicitation of any offer to subscribe or to purchase, shares, units, or other interest in any particular investments. Editor's Note Submitted 2 May 2016 Accepted 14 March 2017 by Stephen J. Brown